Mushrooms-Rich Preparations on Wound Healing: From Nutritional to Medicinal Attributes - Sharifi-Rad, Javad; Butnariu, Monica; Ezzat, Shahira M.; Adetunji, Charles Oluwaseun; Imran, Muhammad; Sobhani, Seyyed Reza; Tufail, Tabussam; Hosseinabadi, Tahereh; Ramírez-Alarcón, Karina; Martorell, Miquel; Maroyi, Alfred; Martins, Natália (Frontiers in Pharmacology, 2020)
Mushrooms have a significant role in human diet as functional food and as a nutraceutical resource. The combination of its umami flavor, protein, vitamins, minerals and carbohydrates has meant that mushrooms could be considered a cheap food source for a long time in many countries. Moreover, mushrooms contain an excellent variety of bioactive metabolites that can be successful in both prevention and treatment of various human health hazards. In addition, extracts from medicinal mushrooms and their metabolites have been verified for wound treating with contribution to different mechanisms of the healing process. This review summarizes the nutritional value and composition of mushrooms, ethnobiology and ethnopharmacology, and wound healing potential.